Provisioning Firearms in Latin America: Historical Development and Societal Consequences. (June 2022) - Witkowski, Terrence H.
For hundreds of years, the systems provisioning firearms to Latin America states, insurgents, markets, and criminals have had important societal consequences. The constant supply of guns has accelerated widespread violence at an individual level that in the aggregate has facilitated colonial rule, brutal institutions of slavery, numerous insurrections and border wars and, in more recent times, drug trafficking and the social disruption of communities. Firearms also have enabled national independence movements, hunting for necessary sustenance, physical protection from animal and human predators, and the enjoyment of shooting sports past and present. This article provides an account of Latin American firearms provisioning from the time of European arrival and conquest into the twenty-first century and considers some of the many ensuing societal effects. Historical research, a key component of the macromarketing domain, provides a broader understanding of firearms and gun cultures in the region.